2006
DOI: 10.1074/jbc.m509775200
|View full text |Cite
|
Sign up to set email alerts
|

The Presumptive Phosphatidylserine Receptor Is Dispensable for Innate Anti-inflammatory Recognition and Clearance of Apoptotic Cells

Abstract: The role of the presumptive phosphatidylserine receptor (PSR) in the recognition and engulfment of apoptotic cells, and the antiinflammatory response they exert, has been of great interest. Genetic deficiency of PSR in the mouse is lethal perinatally, and results to date have been ambiguous with regard to the phagocytic and inflammatory phenotypes associated with that deficiency. Recently, we found that the specific functional recognition of apoptotic cells is a ubiquitous property of virtually all cell types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 34 publications
(71 reference statements)
4
54
0
Order By: Relevance
“…5 However, recent studies suggest considerable ambiguity regarding the localization of PSR on the cell surface 29 and whether it is crucial for the clearance of apoptotic cells. 30,31 The results of previous studies have demonstrated that CD14 and CD36 are involved in the phagocytosis of apoptotic cells as membrane receptors in HMDMs. However, CD14 appears unlikely to bind preferentially to apoptotic-cell-associated PS, and does not function as a PS-receptor on HMDMs.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, recent studies suggest considerable ambiguity regarding the localization of PSR on the cell surface 29 and whether it is crucial for the clearance of apoptotic cells. 30,31 The results of previous studies have demonstrated that CD14 and CD36 are involved in the phagocytosis of apoptotic cells as membrane receptors in HMDMs. However, CD14 appears unlikely to bind preferentially to apoptotic-cell-associated PS, and does not function as a PS-receptor on HMDMs.…”
Section: Discussionmentioning
confidence: 99%
“…In conceiving the strategy, several criteria guided us: the use of natural, well-defined and safe materials; the treatment should be minimally invasive; and the principles underlying the strategy to resolve inflammation should mimic the anti-inflammatory effects of apoptotic cell clearance by macrophages (16).…”
Section: Discussionmentioning
confidence: 99%
“…Jmjd6 was first thought to be a cell-surface receptor responsible for the recognition and phagocytosis of apoptotic cells (11). However, various following studies showed that Jmjd6 is localized in the nucleus (12)(13)(14)(15)(16) and is not involved in apoptotic cell clearance (17). Subsequently, a function as a histone arginine demethylase was identified (18) and a recent publication suggests that Jmjd6 regulates splicing by hydroxylating the splicing factor U2AF65 (19).…”
mentioning
confidence: 99%